Evaluation of Antibiotic Use in Inpatient and Outpatient Diabetic Ulcer Patients at a Government Hospital in Bandung - Sutrisno, Entris; Anggriani, Ani; Sodik, Jajang Japar (Sciences of Pharmacy, 2025)
Diabetic foot ulcers are caused by neuropathy and/or peripheral arterial disease in patients with type 2 diabetes mellitus. These infections are commonly treated with empirical antibiotics. However, excessive or inappropriate antibiotic use may lead to resistance and poor treatment outcomes. This study aimed to evaluate antibiotic prescribing patterns, rationality, and potential drug interactions in diabetic ulcer patients at a government hospital in Bandung from January to December 2023. A retrospective observational design was used to analyze medical records of 63 patients. The most frequently used single antibiotics were ceftriaxone (51%), cefixime (20%), and ceftizoxime (17%), while the most common combination therapy was ceftizoxime + metronidazole (24%). Evaluation of antibiotic rationality showed 100% appropriate indication, 90.48% appropriate drug selection, and 98.41% appropriate dosage. Despite this, 33.33% of prescriptions had potential drug interactions with commonly co-prescribed medications. These findings indicate generally rational antibiotic use with areas for improvement in drug selection and interaction management. The study highlights the importance of continuous monitoring and rational prescribing to prevent antimicrobial resistance and ensure patient safety.